Pengaruh Kualitas Pelayanan Air Bersih dan Harga Terhadap Kepuasan Pelanggan Perumda Tirta Bhagasasi Cabang Cibarusah - Siregar, Muhammad Reza Hanafi; Izzah, Nidaul (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Customer satisfaction is a state where consumers’ needs, desires, and expectations are met after using a product or service. It serves as a benchmark that companies strive to improve in order to achieve their goals. This is particularly important for companies in the clean water working to enchance customer satisfaction by improving servis quality. This study aimed to analyze the impact of service quality and pricing on customer satification at Perumda Tirta Bhagasasi’s Cibarusah branch. A sample of 100 respondents was selected using random sampling techniques. This research emloyed quantitative methods with data analysis conducted through SPSS 25.0. the data analysis indicated that service quality and pricing countribute to increase in customer satification by 70,7%. Limitations of this study included a relatively small sample size, limited respondents and research variables that did not encompass all possible factors. Future research is advised to borden the respondent base, increase that sample size, and incorporate additional variable related to customer satisfaction